Explicating muslim family communication strategies for peace in Thailand’s deep south / Sakiroh Yaena Benharoon. - Benharoon, Sakiroh Yaena (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2019)
Family communication is a way of exchanging verbal and nonverbal messages among family members. It is basic, small but vital in any society, particularly Muslim communities in the southernmost provinces of Pattani, Yala, Narathiwat and some parts of Songkhla, Thailand, as it cultivates and raises righteous members. Through family communication, members tend to feel at ease to express their thoughts, feelings, needs, love, admiration and connection to one another. It is not only relationships, but also an atmosphere that creates better understanding and peaceful relationships among members in the family. In the ongoing southern unrest and violence, family communication is the best way to build warm relationships and trust among family members. This article aims to discuss the four strategies of Muslim parents in the south of Thailand have done to develop good lines of communication to build peace in family. These include creating time for talking, being active listeners, paying attention to non-verbal messages, and greeting any members with the Islamic greeting. Therefore, effective communication in a family plays an important role to foster and strengthening relationship among family members.